2000
DOI: 10.1021/ja9930824
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurements and Modeling of Kinetics in Nucleic Acid Monolayer Films Using SPR Spectroscopy

Abstract: We report a quantitative study of the kinetics of formation for a two-component tethered ssDNA monolayer film using in situ two-color surface plasmon resonance (SPR) spectroscopy. The attachment of the DNA to gold is facilitated by functionalization at the 5′ end with a thiol group connected by a hexamethylene linker (HS-C6-ssDNA). Detailed data analysis is performed by quantitative comparison of the DNA coverage versus time kinetic data obtained from SPRS with numerical solutions for the differential equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
250
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(267 citation statements)
references
References 27 publications
14
250
2
1
Order By: Relevance
“…In this section, we examine the effect of electrostatic charging on target͞probe hybridization. The DNA monolayer films used in this work have been extensively characterized by SPR, neutron scattering, and surface melting experiments and are found to be robust and reusable (8,9,25). For these experiments, hybridization was allowed to proceed with no potential applied, then the potential was swept at a rate of 50 mV s Ϫ1 to the desired potential (ϩ300 mV or Ϫ300 mV), and hybridization allowed to continue.…”
Section: Spr Detection In the Presence Of An Applied Electrochemical mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we examine the effect of electrostatic charging on target͞probe hybridization. The DNA monolayer films used in this work have been extensively characterized by SPR, neutron scattering, and surface melting experiments and are found to be robust and reusable (8,9,25). For these experiments, hybridization was allowed to proceed with no potential applied, then the potential was swept at a rate of 50 mV s Ϫ1 to the desired potential (ϩ300 mV or Ϫ300 mV), and hybridization allowed to continue.…”
Section: Spr Detection In the Presence Of An Applied Electrochemical mentioning
confidence: 99%
“…The ordinate is given as percentage of steady-state hybridization. That is, the DNA coverage is calculated from analysis of the SPR reflectance curves as described previously (8,9,24,25). The progress of hybridization is shown as the percent of the duplex DNA surface coverage relative to the steady state coverage achieved after Ϸ14 h of hybridization at open circuit.…”
Section: Spr Detection In the Presence Of An Applied Electrochemical mentioning
confidence: 99%
“…Modeling studies with thiolated DNA have demonstrated that efficient hybridization occurs in the well-controlled condition of surface-attached probes with large interprobe distances and upright conformations. [13][14][15][16][17][18][19][20][21][22][23][24] However, constructing a reproducible DNA recognition layer with both of these properties is a critical challenge owing to unexpected surface adsorptions, disordered conformations, inconsistencies in grafting density and the flexibility of probe molecules. It is thus imperative to obtain an in-depth understanding of the factors that influence the structure of immobilized DNA layers.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies with thiolated DNA have demonstrated that efficient hybridization occurs in the well-controlled condition of surface-attached probes with large interprobe distances and upright conformations. [13][14][15][16][17][18][19][20][21][22][23][24] …”
mentioning
confidence: 99%
“…Adsorption of DNA oligomers on gold electrode is a complicated kinetic process [32]. Until now one of the most common strategies for DNA immobilization on gold electrode is the formation of thiolated DNA self-assembly monolayer (SAM) via the strong Au-S bond.…”
Section: Resultsmentioning
confidence: 99%